Ocean and Beyond: A Benthic Imagination of the Black Historiography in August Wilson’s Gem of the Ocean and Henry Dumas’s “Ark of Bones” - Mondal, Biman; Rahman, Md Mojibur; Mukhopadhy, Tuhin (Journal of Ecohumanism, 2024)
Ocean can be read as a mnemonic text, from anthropological, historiographical, sociological, and literary perspectives, despite ocean being constructed, in our popular imagination, as a void –a ‘non-place’ in Mark Auge’s term.Ocean, in general, symbolizes chaos. The present studyseeks to identify the symbolic and material connotation of ocean water,recognizing how ocean becomes an integral part of African-American diasporic identity, cultural, and historiographic legacy, predicated on a mnemonic context, as represented in August Wilson’s play Gem of the Ocean and Henry Dumas’s short-story “Ark of Bones,” bringing out a literary-historical dimension of ocean water, closely linked with identity-formation.